Conveyer belt, workers and buildings at Pacific American Fisheries cannery at Port Moller, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: Belt conveyer, Cannery, Port Moller, Aaa. PH Coll 247.915 Port Moller is a village in southwest Alaska. It is located on the Alaska Peninsula at the entrance of Port Moller Inlet (20 mi long) of Bristol Bay on the Bering Sea. Primary industries are fishing and fish canning.